Resolution Transfer in Cancer Classification Based on Amplification Patterns - Adhikari Prem Raj; Hollmén Jaakko (Switzerland, 2022)
In the current scientific age, the measurement technology has considerably improved and diversified producing data in different representations. Traditional machine learning and data mining algorithms can handle data only in a single representation in their standard form. In this contribution, we address an important challenge encountered in data analysis: what to do when the data to be analyzed are represented differently with regards to the resolution? Specifically, in classification, how to train a classifier when class labels are available only in one resolution and missing in the other resolutions? The proposed methodology learns a classifier in one data resolution and transfers it to learn the class labels in a different resolution. Furthermore, the methodology intuitively works as a dimensionality reduction method. The methodology is evaluated on a simulated dataset and finally used to classify cancers in a real–world multiresolution chromosomal aberration dataset producing plausible results.
Discovery Science: 18th International Conference, DS 2015, Banff, AB, Canada, October 4-6, 2015. Proceedings